The radical-based reduction with (TMS)3SiH 'on water' - Postigo, Jose Alberto (2005)
Reduction of different organohalides, bromonucleosides among them, was successfully carried out in yields ranging from 75% to quantitative, using (TMS)3SiH in a heterogeneous system with water as the solvent. Our procedure, employing 2-mercaptoethanol as the catalyst and the hydrophobic diazo-compound ACCN as the initiator, illustrates that (TMS)3SiH can be the radical-based reducing agent of choice in aqueous medium. (TMS) 3SiH does not suffer from any significant reaction with water and can safely be used with additional benefit, such as ease of purification and environmental compatibility.